The Importance of Network Contract Model for SMEs` Growth. The Case of an Italian Region - Granata, Giuseppe (European Scientific Journal, ESJ, 2017)
Aim: The aim of this paper is to analyze the strategic validity of Italian network contract in order to define a new business model for contemporary enterprises. Methodology: The research method is deductive-inductive with a multimethod approach. The sources are collected through semi-structured interviews and open sources, scientific books and papers, and sectorial database. Findings: The present research is the first step taken in conducting an extended study on a territorial, regional, and national level. Limitations: Research limitations are based on the restricted data used in the present phase of the work. Implications: The paper aim at integrating existing literature for academic community and decision makers. Originality: The research represents essential characteristics of Italian network contract, by emphasizing its framework and validity, in order to recognize an innovative business model in increasing the enterprises competition in the market.